Pengaruh Strategi Promosi dan Harga terhadap Kepuasan Pelanggan pada UMKM Kuliner - Azizah Mutiara; Rendi Juanda; Dian Purnamasari (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the influence of promotional and pricing strategies on customer satisfaction and their impact on customer satisfaction at the Mie Ayam Mamak Bayu culinary MSME located in Deli Serdang Regency, North Sumatra. The research problem stems from the fluctuation in the number of customers despite the implementation of certain promotions and pricing. The research approach used is quantitative with a survey method. Primary data were collected by distributing questionnaires to 30 active customers selected by purposive sampling. The data analysis technique used multiple linear regression through SPSS software. The results of the F test showed that promotional and pricing strategies simultaneously had a significant effect on customer satisfaction (F = 19.610; p = 0.000). Partially, promotional strategies (t = 2.745; p = 0.010) and prices (t = 3.129; p = 0.004) had a positive and significant effect on customer satisfaction. Customer satisfaction was also proven to significantly influence consumer satisfaction (t = 5.712; p = 0.000). These findings indicate that effective promotions and appropriate prices can shape customer satisfaction and loyalty. This research provides strategic recommendations for MSMEs to design targeted promotions and prices to increase business competitiveness.